Pendampingan Kader Jumantik Untuk Menurunkan Kejadian DBD Di Desa Magepanda Kabupaten Sikka - Gabriel Mane; Maria K. Ringgi Kuwa; Yustina Wela; Petronela Lito; Laurentina Nona Eda (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Dengue Hemorrhagic Fever is one of the infectious diseases that still exist every year. The most appropriate prevention of dengue fever is to eliminate the vector of dengue disease, namely mosquitoes. The duties of jumantik cadres are not only as larvae monitors but also as community educators. Educated communities are expected to be actively involved as independent jumantik in their respective homes. Dengue disease in Sikka Regency continues to increase from year to year. In 2019 there were 392 cases and in 2020, rising to 1772 cases with 16 deaths. The large increase made DBD cases in Sikka Regency included in the Extraordinary Event. A low ABJ indicates that the community's PHBS is low, this also shows that people's behavior about PHBS is still low. Magepanda District is one of the sub-districts in Sikka Regency which has 5 villages. One of the villages in Magepanda District is Magepanda Village with 4 hamlets and 21 RT. This Community activity aims to provide learning experiences or create conditions for individuals, groups, families, by opening lines of communication, information, and education to increase knowledge, attitudes, and behavior so that people are aware, willing, and able to practice clean and healthy living behaviors. healthy through a leadership approach, social development, and community empowerment.